Potential Role of Plant Growth-Promoting Halotolerant Bacteria in Enhancing Shallot Growth under Salinity Stress - Arkan Setiaji; Sulastri Sulastri; Didy Sopandie (Universitas Sebelas Maret, 2025)
Soil salinization, driven by seawater intrusion, significantly challenges agricultural productivity in coastal regions. Horticultural crops, such as shallots, are especially sensitive to salinity stress, which impairs growth, nutrient uptake, and bulb yield. This study explored halotolerant plant growth-promoting bacteria from saline soils in East Nusa Tenggara, Indonesia, to reduce salinity stress in shallots. Seventeen bacterial isolates were screened for halotolerance, and eight of them were capable of growing at 1,250 mM NaCl (OD600 ≥ 0.5). Selected halotolerant isolates also exhibited the ability to produce indole-3-acetic acid (IAA) and exopolysaccharides (EPS), solubilize P, K, and Zn, produce siderophores, and exhibit 1-aminocyclopropane-1-carboxylate (ACC) deaminase activity with varying tolerance at salinity levels up to 1,000 mM NaCl. Inoculation with these isolates significantly improved shallot seedling growth under 90 to 230 mM NaCl, with Enterobacter hormaechei demonstrating the best performance. Bacterial inoculation elevated 47 to 64% proline and 15 to 107% NO3− levels in shallot leaves compared to uninoculated plants, contributing to osmotic adjustment and enhanced nutrient assimilation under salt stress in laboratory trials. Single-strain (E. hormaechei) and a consortium of compatible strains (E. hormaechei strain R11 and M119.1, Klebsiella pneumoniae strain A95, K. variicola strain R198, and Pseudochrobactrum asaccharolyticum strain C167.1) inoculation significantly increased shoot dry weight (100% and 69% each) compared to uninoculated plants under salt stress. These findings advance the current understanding of microbial-assisted salinity mitigation and support broader strategies for climate-resilient, sustainable agriculture in saline-prone coastal regions.